The Influence of Brand Image and Price on Purchase Decision: Study on One E-Commerce - Sintiya Sintiya; Boy Suzanto (Majalah Bisnis & IPTEK, 2023)
The motivation for this study stems from the intense competition observed among e-commerce platforms during the consumer's purchasing process. One potential approach to tackle this issue is through the proficient execution of a brand image strategy with the aim of augmenting sales. Brand image activities typically center around establishing pricing strategies and facilitating purchasing decisions, which collectively form an integral component of the marketing mix. The employed research methodology is a quantitative approach incorporating descriptive and verificative methods. The study's sample comprises 100 participants who have engaged in shopping activities on an electronic commerce platform. The results of this study suggest that (1) Brand image exerts a favorable and substantial influence on consumer purchasing decisions, and (2) Price exerts a significant and positive effect on consumer purchasing decisions.